Growth and poverty : the development experience of Bangladesh - Ahmed, Sadiq; Mahmud, Wahiduddin; World Bank.; University of Dhaka. Bureau of Economic Research (Dhaka : The University Press, 2006)
Contributed articles presented at a seminar held in Dhaka during June 26-27, 2003 organized at Bureau of Economic Research, University of Dhaka and with support of World Bank.
Includes bibliographical references and index.
ESS
Keywords: Poverty -- Bangladesh -- Congresses; Bangladesh -- Economic policy; Bangladesh -- Social policy; Economics